Evaluation and genome-wide association study of saline–alkali tolerance in high-latitude rice resource populations - Wang, Rongsheng; Lv, Tan; Li, Jingpeng; Ma, Juntao; Wang, Yongli; Deng, Lingwei; Li, Wan; Zhang, Jun; Li, Kun; Zhang, Wei; Mu, Fengchen; Zhang, Guomin (Frontiers in Genetics, 2025)
IntroductionChina is the world’s third largest saline–alkali land country, and the breeding of salt-tolerant rice varieties has always been a key focus of rice breeders. Screening and identifying salt-tolerant varieties and exploring related genes are essential for breeding.MethodsIn this study, 450 high-latitude resource populations were planted on natural saline–alkali soil for 2 years under 2 treatments. The comprehensive agronomic traits of the populations were evaluated. The principal component and cluster analyses were used to preliminarily group the phenotypes, and individual phenotypes were comprehensively scored and ranked to identify the top 40 saline–alkali tolerant varieties each year.ResultsNotably, S321 and S19 were the most saline-alkali tolerant varieties each year. Genome-wide association studies identified one saline–alkali-related position near 6,636,119 bp on chromosome 8 and another near 23,311,931 bp on chromosome 11. Os08g0214233 and Os11g0604900 were the nearest genes from the identified positions, respectively. Gene annotation was used to further screen the polymorphic sites in the associated regions, identifying 17 and 48 genes with 593 variants, including 56 polymorphic sites located in exons.DiscussionThis study provided candidate gene loci for the fine mapping of saline–alkali tolerance genes and offered excellent resistant rice resources for the molecular improvement of varieties.